Harnessing food system equity from the ground up: shifting co-governance practices in the funding of food security responses during the pandemic crisis in Toronto, Canada. - Regnier-Davies, Jenelle; Edge, Sara (Food, Culture & Society, 2025)
The COVID-19 pandemic was a disrupting force that magnified social inequities and service gaps in underserved urban communities. It was also a "window of opportunity" for the Black Lives Matter movement and Indigenous reconciliation synergies to spur calls to action for more open and inclusive dialog regarding community food security. Increasingly, community-based organizations (CBOs) that have not been traditionally food-focused are becoming more involved in food security responses. These factors have offered space to revisit antiquated and exclusionary practices within resource allocation and decision-making processes that reinforce systems of oppression within the food system. We explore the interconnection between CBOs, municipal actors, and funders in Toronto and draw upon the concept of co-governance to unpack their evolving relationships and influence on equity-focused change in policies and practices. Based on an analysis of interviews (n = 48), this paper articulates that a number of realized progressive, yet incremental, changes have been made, including changes to policies and internal practices and targeted support for Black and Indigenous communities. However, ultimately, a transfer of resources and influence is required in order to achieve the broader goal of harnessing food system equity.